DAMPAK IMPOR CABAI DARI TIONGKOK TERHADAP PEREKONOMIAN INDONESIA TAHUN 2010-2015 - Arya Yuwedly Maramis; Syafri Harto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research is a study of international relations in the field of international political economy. This research will discuss the impact of chili imports from China in the Indonesian economy 2010-2015. Indonesia imports chili pepper from China to meet the high market demand. This needs to be done so that the market price of chili is not too high so people can afford it. Chili imports by Indonesia in large quantities have caused new problems. Chili farmers in Indonesia suffered losses due to the low price of chilies they produce.In discussing the impact of chili imports from China on the Indonesian economy in 2010-2015 the authors use a qualitative research methodology with data collection techniques library research (library research) derived from the sources of literature books, journal publications and various scientific articles. The perspective used is mercantilism. The level of analysis used is the Nation-State. Theory used is Import-Export Theory.The results of this research indicate that imported chilli made by Indonesia is an important action. However, in importing Indonesia should still pay attention to the amount of chili to be imported. This needs to be done so that local chili produced by Indonesian farmers is not cheap in the market. The government must strictly monitor the number of chili import quotas from China. The Indonesian government should oversee private importers who often import more than their intended quota.Keywords: Import, Chili, Indonesia, China